Full Blood Count and its Differentials in Acute Aortic Dissection: An Update and Future Perspectives - Georgiadou, Panagiota; Elefteriades, John (AORTA, 2025)
Acute aortic dissection (AAD) is a potentially lethal condition with a high rate of misdiagnosis during the initial evaluation. In addition to established clinical variables, previous studies have consistently demonstrated a relationship between full blood count (FBC) and its various differentials with acute aortic syndromes, even identifying patients with worse outcome. Although FBC is a simple, inexpensive and routinely performed test, it is easily overlooked by clinicians. However, nearly all components of FBC, including white blood count, red blood cells, and platelets, may contribute to the underlying pathogenesis of AAD and therefore, we should fully explore and pinpoint precisely their potential diagnostic or prognostic performances. Herein, we summarize the results of such studies and discuss controversies regarding utility in future clinical practice.
Keywords: acute aortic dissection; biomarkers; full blood count; diagnosis; aneurysm